Effective therapies for sickle cell disease: are we there yet?. Issue 12 (December 2022) - Crossley, Merlin; Christakopoulos, Georgios E.; Weiss, Mitchell J.
Abstract : Sickle cell disease (SCD) is a common genetic blood disorder associated with acute and chronic pain, progressive multiorgan damage, and early mortality. Recent advances in technologies to manipulate the human genome, a century of research and the development of techniques enabling the isolation, efficient genetic modification, and reimplantation of autologous patient hematopoietic stem cells (HSCs), mean that curing most patients with SCD could soon be a reality in wealthy countries. In parallel, ongoing research is pursuing more facile treatments, such as in-vivo -delivered genetic therapies and new drugs that can eventually be administered in low- and middle-income countries where most SCD patients reside. Highlights: β-Hemoglobinopathies result from homozygous or compound heterozygous β-globin HBB gene mutations that affect the function or production of the β-globin subunit of adult-type hemoglobin (Hb; α2β2). Persistence of high-level γ-globin HBG gene expression after birth resulting in the production of fetal Hb α2γ2 can alleviate β-hemoglobinopathies. β-Hemoglobinopathies are among the world's most prevalent disorders due to evolutionary selection for malaria resistance in heterozygous carriers. Sickle cell disease (SCD), caused mainly by homozygosity for the HBB p.Glu6Val mutation, is a particularly common β-hemoglobinopathy, and was the first genetic disorder characterised at a molecular level. Now, >60 years later, numerous mechanism-based somatic gene therapies are being examined in clinical trials on small numbers of patients. Ultimately the broad scientific knowledge gained by studying globin biology will inform the development of effective drugs that can be administered to many SCD individuals and those affected by other β-hemoglobinopathies worldwide.